DINAMIKA BISNIS TRAVEL UMROH SE KOTA PASURUAN DI ERA GLOBALISASI - Dewi Masitah (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
This research aims to know how the Ethics and responsibility of  PT TRAVEL Umrah conducts its travel business?. This background research of Various motivations variety PT TRAVEL Umrah in implementing its travel business. Is that motivation is not only a business commodity, so causing a few problems related to that Travel, among others, the cheapness of travel so that the number of Umrah pilgrims displaced and not so depart with many reasons such as the visa is not out or travel unclear. This research is a qualitative research of Phenomenology. The research data obtained through technique of observation, in-depth interviews (in-depth interview), Focus Group Discussion (FGD) and documentation with data analysis using a model of Miles and Huberman, which includes three lines of analysis, namely data reduction (data reduction), a data display (presentation data), and conclusion drawing / verification (conclusion). This Research uses the perspective of Petter Beyyer related to a religious commodity for the sake of a capitalist. Business in the name of religion is a commodity.